Immunoglobulin replacement therapies in inborn errors of immunity: a review - Sil, Archan; Basu, Suprit; Joshi, Vibhu; Pilania, Rakesh Kumar; Siniah, Sangeetha; Suri, Deepti; Rawat, Amit; Singh, Surjit (Frontiers in Pediatrics, 2024)
Immunoglobulins (Ig) were used as a therapeutic modality for the first time in a patient with X-linked agammaglobulinemia in 1952 by Colonel Odgen Bruton, decades before the molecular mechanisms causing the disease were unraveled. In many autoimmune and inflammatory illnesses, human immunoglobulin has been employed as a significant immunomodulatory and immunosuppressive drug. In patients with inborn errors of immunity (IEI), immunoglobulin remains a cornerstone of management. IEIs are notable causes of recurrent infections and autoimmunity due to inheritable single-gene defects in genes encoding for different components of the immune system. As there is decreased immunoglobulin production in IEIs with antibody defects, immunoglobulin replacement is the mainstay of therapy in these disorders. Although serum immunoglobulin levels may not be low in combined immune defects, immunoglobulin replacement is still necessary in these disorders due to a deficiency of functional antibodies and qualitative defects of immunoglobulins. Commercial immunoglobulin preparations are generated from plasma donated by thousands of donors. Immunoglobulin preparations are usually available in two forms: intravenous and subcutaneous immunoglobulins. In the developed world, both intravenous immunoglobulin (IVIg) and subcutaneous immunoglobulin (SCIg) are available, and SCIg is preferred over IVIg for replacement therapy in patients with IEIs. In developing countries, IVIg remains the mainstay of replacement therapy. The rate of adverse events has significantly reduced over the last few years due to advancements in the production process. In this review article, we discuss different aspects of the use of Ig (indications, dosing, mechanism of action, route, adverse effects) in patients with IEIs.